Revised Ordinances of the City of Fitchburg 179 (1893) - (:unkn) unknown (My University, 1893)
Fitchburg Revised Ordinances. §§ 75-76: No person shall sell or keep for sale, within the limits of the city of Fitchburg, any toy pistol, toy cannon, or any other such article in which explosive compounds of any kind are used, or of which such compounds form a part. § 76. No person shall have, use, explode, fire off or discharge, within the limits of the city of Fitchburg, any toy pistol, toy cannon, or any other such article in which explosive compounds of any kind are used, or of which such compounds form a part.
Keywords: DISCHARGE; TRANSFER, MANUFACTURE & POSSESSION - TOYS AND EXPLOSIVES